Fenfluramine: a plethora of mechanisms? - Sourbron, Jo; Lagae, Lieven (Frontiers in Pharmacology, 2023)
Developmental and epileptic encephalopathies are rare, treatment-resistant epilepsies with high seizure burden and nonseizure comorbidities. The antiseizure medication (ASM) fenfluramine is an effective treatment for reducing seizure frequency, ameliorating comorbidities, and potentially reducing risk of sudden unexpected death in epilepsy (SUDEP) in patients with Dravet syndrome and Lennox-Gastaut syndrome, among other rare epilepsies. Fenfluramine has a unique mechanism of action (MOA) among ASMs. Its primary MOA is currently described as dual-action sigma-1 receptor and serotonergic activity; however, other mechanisms may be involved. Here, we conduct an extensive review of the literature to identify all previously described mechanisms for fenfluramine. We also consider how these mechanisms may play a role in the reports of clinical benefit in nonseizure outcomes, including SUDEP and everyday executive function. Our review highlights the importance of serotonin and sigma-1 receptor mechanisms in maintaining a balance between excitatory (glutamatergic) and inhibitory (γ-aminobutyric acid [GABA]-ergic) neural networks, and suggests that these mechanisms may represent primary pharmacological MOAs in seizures, nonseizure comorbidities, and SUDEP. We also describe ancillary roles for GABA neurotransmission, noradrenergic neurotransmission, and the endocrine system (especially such progesterone derivatives as neuroactive steroids). Dopaminergic activity underlies appetite reduction, a common side effect with fenfluramine treatment, but any involvement in seizure reduction remains speculative. Further research is underway to evaluate promising new biological pathways for fenfluramine. A better understanding of the pharmacological mechanisms for fenfluramine in reducing seizure burden and nonseizure comorbidities may allow for rational drug design and/or improved clinical decision-making when prescribing multi-ASM regimens.